Sensor technology handbook - Wilson, Jon S. (Elsevier, 2005)
Without sensors most electronic applications would not existthey perform a vital function, namely providing an interface to the real world. The importance of sensors, however, contrasts with the limited information available on them. Today's smart sensors, wireless sensors, and microtechnologies are revolutionizing sensor design and applications. This volume is an up-to-date and comprehensive sensor reference guide to be used by engineers and scientists in industry, research, and academia to help with their sensor selection and system design. It is filled with hard-to-find information, contributed by noted engineers and companies working in the field today. The book will offer guidance on selecting, specifying, and using the optimum sensor for any given application. The editor-in-chief, Jon Wilson, has years of experience in the sensor industry and leads workshops and seminars on sensor-related topics. In addition to background information on sensor technology, measurement, and data acquisition, the handbook provides detailed information on each type of sensor technology, covering: technology fundamentals sensor types, w/ advantages/disadvantages manufacturers selecting and specifying sensors applicable standards (w/ urls of related web sites) interfacing information, with hardware and software info design techniques and tips, with design examples latest and future developments The handbook also contains information on the latest MEMS and nanotechnology sensor applications. In addition, a CD-ROM will accompany the volume containing a fully searchable pdf version of the text, along with various design tools and useful software. *The only comprehensive book on sensors available! *Jam-packed with over 800 pages of techniques and tips, detailed design examples, standards, hardware and software interfacing information, and manufacturer pros/cons to help make the best sensor selection for any design *Covers sensors from A to Z- from basic technological fundamentals, to cutting-edge info. on the latest MEMS and the hottest nanotechnology applications.